Společenské klima v ČR – percepce občany - Brychtová, Šárka (Univerzita Pardubice, 2007)
The article deal with the problematics of the reception of the sociable clime by the citizens of Czech Republic. It is created by virtue of interview elaborated in the spring 2007 and in its virtue of it try to interprets view of the czech inhabitans to the prezent course of the events by aspect not only economical and political, but also sociable a social. It tries to catch the atmosphere of certain first intergenerational nuance.
Keywords: development of society; sociable atmosphere; social imbalance; political culture